2020
DOI: 10.7759/cureus.9499
|View full text |Cite
|
Sign up to set email alerts
|

Survival of the Fittest: Addressing the Disparities in the Burden of Chronic Kidney Disease

Abstract: The prevalence of chronic kidney disease (CKD) is increasingly becoming recognized as a global health concern as well as a critical determinant of poor health outcomes. Decreased access to health care and low socioeconomic status (SES) worsen the adverse effects of biologic or genetic predisposition to CKD. All the studies used were retrieved using the PubMed database. The literature suggests that in developing and developed countries, lower SES is inversely proportional to CKD. It shows an inconsistent relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Previous studies have produced convincing evidence for an inverse relationship between SEP and manifest kidney disease 33 , but few studies have examined the association between SEP and cystatin C as a subclinical biomarker for early kidney disease. Peralta et al (2006) have reported an association between income and cystatin C in African Americans consistent to the results of the present study 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have produced convincing evidence for an inverse relationship between SEP and manifest kidney disease 33 , but few studies have examined the association between SEP and cystatin C as a subclinical biomarker for early kidney disease. Peralta et al (2006) have reported an association between income and cystatin C in African Americans consistent to the results of the present study 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion criteria included patients who were >18 years of age, CKD stages 1–4, who had controlled hypertension (blood pressure < 140/90 mm Hg) and diabetes mellitus (HbA1C < 7%), attending the KOPD clinic for at least 6 months and were able to provide informed consent. Patients who had active infections, active malignancies, autoimmune diseases and who were not black were excluded, black patients have an increased risk of developing CKD and end stage kidney disease (ESKD) at significantly higher rates than other races [ 13 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that African-Americans have a 2- to 4-fold greater risk for end stage kidney disease (ESKD) requiring renal replacement therapy than their white counterparts [ 10 , 11 ]. Individuals of black ethnicity due to their genetics, including the presence of APOL1 high-risk genotypes, are at higher risk of death due to CKD as a result of social, economic and medical causes [ 12 , 13 ]. African ancestry has been associated with higher serum creatinine levels, lower eGFR estimates and more rapid CKD progression [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients who had active infections, active malignancies, autoimmune diseases and who were not black were excluded. Black patients have significantly higher rates of more rapid CKD progression and ESKD than other races (21, 22), hence they were the focus of this study.…”
Section: Methodsmentioning
confidence: 99%